2011
DOI: 10.1177/0009922811404699
|View full text |Cite
|
Sign up to set email alerts
|

Management of Primary Spontaneous Pneumothorax in Children

Abstract: Recurrence after the first episode of PSP in children is frequent and is difficult to predict by CT findings. VATS is safe and effective in preventing recurrences. Surgical intervention may be an attractive alternative in patients who require chest tube drainage for the first episode of PSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
64
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 31 publications
0
64
0
1
Order By: Relevance
“…The role of blebs/bullae as a preexistent lesion for development of PSP has been questioned; in fact, some studies observed no correlation between its presence and the risk for PSP recurrence (6,8,9,11,12,(14)(15)(16)(17). However, there is some evidence on the lack of association between blebs and different recurrent patterns of PSP (ipsilateral or contralateral).…”
Section: Discussionmentioning
confidence: 99%
“…The role of blebs/bullae as a preexistent lesion for development of PSP has been questioned; in fact, some studies observed no correlation between its presence and the risk for PSP recurrence (6,8,9,11,12,(14)(15)(16)(17). However, there is some evidence on the lack of association between blebs and different recurrent patterns of PSP (ipsilateral or contralateral).…”
Section: Discussionmentioning
confidence: 99%
“…5,10,20,21) The incidence of blebs/bullae on HRCT scans in paediatric population studies was reported to range from 30.8% to 100%, 6,14,17,19,20,22) and the recurrence rate after conservative treatment in patients with air-containing lesions was reported to range from 50% to 100% (Table 4). 6,17,19) These results are consistent with the results of our study of an incidence of blebs/bullae on HRCT scans of 55.3% (63/114) and the 60.3% recurrence rate associated with blebs/bullae on HRCT scans. However, prior studies in the paediatric population were limited by the small number of enrolled patients, which mitigates the significance of the association between air-containing lesions on CT scans and the recurrence of paediatric PSP.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Surgery represents the most effective method for preventing recurrence. However, prevention of recurrence after an initial episode of PSP in children remains controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that CT itself is poor for bleb identification, and that recurrence rates are similar between those with and without blebs. 11,12 In addition, an evidence-based management article from 2009 stated that there is no indication for the use of CT for bleb or bullae assessment after the initial occurrence of SP, 13 and this is in concordance with a 2001 consensus statement from the American College of Chest Physicians (ACCP). 14 However, a retrospective review from 2013 of 114 children undergoing conservative management after primary PSP found that the presence of blebs or bullae on high-resolution CT was a significant risk factor for ipsilateral recurrence.…”
Section: Management Of Spontaneous Pneumothoraxmentioning
confidence: 64%